Tobin-Q, Liquidity and Momentum risk-premia: A Demonstration of Weighted Least Squares Regression Approach - Azam, Mohammad (SEISENSE (PRIVATE) LIMITED, 2023)
Purpose- The basic purpose of the study is to examine whether Tobin-q, liquidity and momentum risk-premium contributes the explanatory power in terms of explaining portfolio returns in PSX. Design/Methodology- The Weighted Least Square (WLS) regression technique is empirically used to examine the nexus between risk-factor and portfolio returns using PSX dataset. The models provide useful tools for making efficient strategies in the jurisdiction of investments and portfolio constructions. Findings- The study reveals that multidimensional liquidity exhibits weak significant results while Tobin-q and momentum risk-factors demonstrate statistically significant determinants for PSX. Furthermore, WLS regression produces robust coefficient results than OLS regression as except liquidity all the factors exhibit substantially improved results. Practical Implications- The study findings would be useful for stocks and portfolio managers constructing optimal and diversified portfolios while investing in PSX.